THEORETICAL ANALYSIS OF BINAHONG LEAF EXTRACT AS CORROSION INHIBITOR USING THE DFT METHOD - Putri, Yunike; Emriadi; Imelda (JURNAL KATALISATOR, 2024)
Binahong leaf extract has been experimentally tested containing several compounds that are effective used as corrosion inhibitors. Further computational chemical research was conducted to determine the interaction of the compounds contents, including vitexin, ursolic acid and p-coumaric acid with the iron using the Density Functional Theory (DFT) method based on B3LYP/6-31G. Quantum chemical parameters from optimization results include EHOMO, ELUMO, dipole moment, energy gap (ΔE), electronegativity (χ), ionization potential (I), electron affinity (A), hardness (η), softness (σ), electrophilicity (ω) and nucleophilicity (ε). The interaction strength parameters of the inhibitor with Fe atom, namely charge transfer (ΔN), interaction energy (Δψ) dan back-donation energy (ΔEb-d), indicate that ursolic acid is the best inhibitor molecule. The interaction of inhibitor with Fe (100) seen from the energy of adsorption (Eads) and the bonding energy (Ebinding) suggests that among the three main contents of plant leaf extract, ursolic acid has the highest value of 111.92 kJ/mol with a bond length value of Inh-Fe of 1.91 Å. Binding length data and binding energy indicate that the interaction that occurs is a chemical interaction.